Community structure and diversity of meiofauna in seagrass beds on the eastern coast of Hainan Island, China - Kai Liu; Yuqing Guo; Mingming Zou; Weilin Chen; Wenjia Hu; Jianguo Du (Global Ecology and Conservation)
Seagrass beds are critical marine ecosystems in tropical, subtropical, and temperate coastal waters, serving as highly diverse and productive habitats for numerous marine organisms. Differences in the abundance, diversity, and community structure of benthic invertebrates between seagrass beds and adjacent unvegetated sediments significantly influence the health and stability of the entire food web. However, most studies to date have predominantly focused on macrofauna but overlooked their meiofauna community, which plays an important role in ecosystem function. This study investigated meiofauna communities in seagrass beds and unvegetated habitats at six sites along Hainan Island's eastern coast, China. Four major meiofauna groups were identified, with free-living marine nematodes being dominant (79.5 % abundance, 51 species), followed by benthic copepods, oligochaetes, and polychaetes. The total average meiofauna abundance and biomass were (19.4 ± 10.0) ind·10 cm−2 and (48.8 ± 33.0) μg·10 cm−2, respectively. Seagrass beds had higher abundance and biomass than unvegetated areas, but lower marine nematodes biodiversity. Species richness, evenness, and diversity indices in seagrass beds ranged from 2.00–3.56, 0.49–0.90, and 1.21–2.16, respectively. Furthermore, environmental factors such as dissolved oxygen and chlorophyll content were found to significantly influence the distribution of nematodes and polychaetes. The results highlight the important role of seagrass beds in supporting meiofauna diversity and abundance, which are key contributors to the functioning of the coastal food web. The greater biomass and abundance of meiofauna in seagrass beds compared to unvegetated areas underscore the ecological value of seagrass ecosystems, particularly in maintaining benthic community structure and enhancing trophic interactions.